Pemberdayaan Pojok Baca Melalui Implementasi Gerakan Nasional Gemar Membaca bagi Masyarakat Kampung Poncowati - Mudaim; Suci Ayu Putri; Widya Nurwani; Elisa Anindita; Marsela (Yayasan Inspirasi El Burhani, 2021)
Background: Creating a reading corner at the Village Hall in realizing government programs, especially the national library in carrying out the reading fondness movement, the Poncowati Village community service group established and facilitated a reading corner service that provided various types of books to be used as public reading material. The books were obtained as a grant from the people of Kampung Poncowati and there are 120 titles available consisting of various fields of education, health, agriculture, fisheries, economics, social, culture, religion, and so on. In managing the reading corner, books are still not in accordance with the needs of the community so that public interest in visiting the Reading Corner is still lacking. Therefore, a solution is needed to overcome this problem through a national program for reading fondness. The national movement for reading fondness is one of the means in realizing a dedicated, clean, orderly and united Indonesia. Through reading materials, there is a lot of information related to character messages that have the potential to change the mindset of the Indonesian people for the better in order to advance and educate the Indonesian people. Objective: Increase public awareness in rearranging the Reading Corner to attract reading interest in the people of Kampung Poncowati. Method: This program is implemented through methods of education and training, mentoring, dedication and guidance towards a clean, orderly, mutual cooperation, and service to Indonesia which is expected to be sustainable through the awareness of relevant parties, especially the government and regional libraries in paying attention to village library facilities and infrastructure. which has potential. in realizing the national program of the mental revolution-based reading movement. Through socialization activities for the mental revolution movement through empowerment Results: The implementation of the core program of Establishing the Reading Corner of Poncowati Village went smoothly because of the enthusiasm of the community to visit the Reading Corner of Poncowati Village starting from children, teenagers to adults.